Microwave-assisted MgO NP catalyzed one-pot multicomponent synthesis of polysubstituted steroidal pyridines - Ansari, Anam; Ali, Abad; Asif, Mohd; Shamsuzzaman (New Journal of Chemistry, 2018)
The present study reports a highly efficient and green synthetic route for the synthesis of steroidal pyridines. The synthetic methodology involves a microwave-assisted one-pot multicomponent reaction using MgO NPs as a heterogeneous, mild and reusable catalyst. The synthesized MgO NPs were characterized by FTIR, TGA/DTA and XRD analyses. The remarkable features of this protocol include simple operational procedure, shorter reaction profiles, mild reaction conditions, minimal chemical waste and economic viability. The recyclability of the catalyst and high yield of products make the proposed method a sustainable alternative.